Qualitative research methods for psychologists introduction to empirical studies (Elsevier Academic Press, 2005)
This collection of 14 original articles teaches readers how to conduct qualitative research. Instead of characterizing and justifying certain methods, the contributors show by means of actual research studies what assumptions, procedures, and dilemmas they encountered. Fischer's introduction, which emphasizes the practical nature of qualitative research and the closing chapter, which uses a question-and-answer format to investigate, among other subjects, what is scientific about qualitative research, are complemented by a glossary and other features that increase the book's utility and value. * Addresses a range of practical examples from different traditions such as phenomology, grounded theory, ethnography and discourse analysis through actual case studies * Discusses various methodology and combinations of methods like assimilation analysis, dialogal approach, intuitive inquiry, and conceptual encounter * Terms are defined within chapters and/or in a glossary * Helps readers bridge from experimental to qualitative methods * Provides in-depth, philosophically grounded, and compelling research findings * Includes practical introduction about steps in qualitative research